Cognitive impairment profile in patients with the m.3243A> G variant in mitochondrial DNA - Satu Winqvist; Mikko Kärppä; Jukka S. Moilanen; Kari Majamaa (BMC Neurology)
Abstract Background The m.3243A>G variant in mitochondrial DNA is associated with a wide spectrum of clinical features ranging from asymptomatic subjects to severely symptomatic patients. Cognitive involvement is one of the clinical features, but its severity and frequency are not properly known. Here we describe neuropsychological features associated with m.3243 A > G. Methods We studied 45 adult patients with m.3243 A > G and 45 healthy subjects. Comprehensive neuropsychological test battery was applied. Cognitive impairment was defined, if at least five out of seven cognitive domains were impaired compared to matched controls. Major cognitive impairment was diagnosed, if the impairment was general across the domains. Results Sixteen patients (36%) with m.3243 A > G were diagnosed with cognitive impairment, and six of them (13%) had a major cognitive impairment. The median age at diagnosis of cognitive impairment was 53 years (range, 25–64). The profile consisted of impaired abstract reasoning, memory problems, motor function defects and executive problems. Executive functions were affected most, and verbal memory was affected the least. Higher variant heteroplasmy and more severe global phenotype were associated with cognitive impairment, whereas age and sex were not. Conclusion Cognitive impairment is found frequently in patients with m.3243 A > G, but major cognitive impairment is not common. The impairment affects all neuropsychological domains and no specific profile could be identified.